Study of physicochemical changes of polluted sediments from Reconquista river basin (Argentina) after remediation processes. (2018) - Olivelli, M.S.; Simpson, M.J.; Porzionato, N.F.; Fernández, M.A.; Sánchez, R.M. Torres; Curutchet, G.
The physicochemical properties of sediments and their ability to retain pollutants are affected by both contamination and remediation processes. The aim of this study is to determine structural and physicochemical changes in real sediment contaminated with metals, subjected to bioleaching processes in a previous study. The sediment contaminated with heavy metals and samples of the same sediment treated with different heap leaching tests were used. They were characterised by potentiometric titrations, electrophoretic mobility, organic matter (OM), nuclear magnetic resonance (NMR), volatile solids and sulphides. For contaminated and treated sediment samples, the results of OM, sulphides, volatile solids to 600°, potentiometric titrations and zeta potential values depended on the bioleaching treatment performed previously. The contaminated sediment sample without any bioleaching treatment presented the greatest amount of OM and sulphides. Moreover, metal adsorption isotherms were performed. The contaminated sediment without bioleaching treatment was the one with the highest adsorption capacity. The baseline sample did not present a noticeable adsorption capacity. This study indicates the importance of the contribution of OM and sulphides to sediments and structural and physicochemical studies after remediation treatments.